The role of the dentist in the diagnosis and early detection of neoplastic lesions based on the example of Proliferative verrucous leukoplakia, classified as an OPMD - Stawarz-Janeczek, Magdalena; Łazarz-Bartyzel, Katarzyna; Kiencało, Andrzej; Pytko-Polończyk, Jolanta (Folia Medica Cracoviensia, 2026)
Proliferative verrucous leukoplakia (PVL) was first described by Hansen, Olson, and Silverman in 1985 as a form of hyperkeratosis, remained resistant to treatment and was further distinguished by the aggressive nature of the lesions and a high rate of malignant transformation (MT). The OPMDs classification developed in 2020 recognized PVL as a distinct form of multifocal oral leukoplakia, characterized by a progressive clinical course and with changing clinical and histopathological features. According to WHO, the risk of malignant transformation of PVL among OPMDs is approximately 50%. This frequent MT of PVL involves transformation into VC or OSCC, which, according to various sources in the literature, occurs in between 43.87% and 65.8% of cases, and according to some in up to 70% of cases. Some reports even suggest a possible malignant transformation rate of around 100%. PVL usually occurs in multiple areas of the oral cavity simultaneously and is characterized by slow but continuous progression. The aetiology of PVL and the factors influencing its progression to cancer are unknown. Close monitoring of patients is recommended and, if necessary, biopsies should be performed to assess changes in the appearance, colour, and size of observed lesions, as well as the appearance of subsequent lesions. Early diagnosis, surgical removal, and patient observation are crucial in the treatment of PVL.